What if I Speak Another Language? Many Libraries, Many Languages. Issue 1 (2nd January 2021) - Acevedo, Oriana; Forsyth, Ellen
ABSTRACT: The work of the State Library of New South Wales (SLNSW) with and for NSW public libraries is examined here to highlight public library collections and services for people who speak languages other than English. Three case studies are presented. Together, these studies demonstrate ways in which public libraries support their communities. The first project examined considers the SLNSW's work with the Australian Library and Information Association (ALIA) to seek changes to the Classification (Publications, Films and Computer Games) Act 1995 (NSW). The proposed changes to the Act would enable unclassified films in languages other than English to be purchased in Australia for public libraries. At present unclassified films can only be purchased overseas. The second project reflects on research conducted in 2018 into multicultural public library services across NSW which led to benchmarks for current services and a basis for improvement. Finally, a case study on the SLNSW's work on portable local studies is presented. This is a collaboration with 16 public libraries collecting local studies material in partnership with people from their culturally and linguistically diverse communities. These case studies highlight the social value of this work and offer examples for similar practice across the public library network.